2021
DOI: 10.3390/nu13010216
|View full text |Cite
|
Sign up to set email alerts
|

Does Drinking Coffee and Tea Affect Bone Metabolism in Patients with Inflammatory Bowel Diseases?

Abstract: Patients suffering from Crohn’s disease and ulcerative colitis are at higher risk of osteoporosis due to lower bone mineral density. Risk factors of osteoporosis are divided into unmodifiable, namely, age, gender, genetic factors, as well as modifiable, including diet, level of physical activity, and the use of stimulants. Coffee and tea contain numerous compounds affecting bone metabolism. Certain substances such as antioxidants may protect bones; other substances may increase bone resorption. Nevertheless, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…Caffeine can lead to osteoclastogenesis through the COX-2/prostaglandin E2 (PGE2) pathway [ 16 ]. Consumption of caffeine-containing products may affect the bone metabolism [ 17 ]. Since caffeine has various effects on the bone metabolism, it may affect the OTM as well, particularly if consumed on a daily basis [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Caffeine can lead to osteoclastogenesis through the COX-2/prostaglandin E2 (PGE2) pathway [ 16 ]. Consumption of caffeine-containing products may affect the bone metabolism [ 17 ]. Since caffeine has various effects on the bone metabolism, it may affect the OTM as well, particularly if consumed on a daily basis [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a report found that tea consumption after gastric cancer surgery could promote the recovery of postoperative gastrointestinal function and improve the quality of life of patients [13]. Meanwhile, tea consumption has been shown to improve cognition, mood, and human brain function [14] and somatic function [15]. All these studies show that drinking tea can improve the health condition of cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a high consumption of caffeine may disturb the calcium-phosphate balance. Therefore, patients at risk of osteoporosis should consume a limited portion of tea [34,35].…”
Section: Introductionmentioning
confidence: 99%